Characterization and Functional Analysis of a Type 2 Diacylglycerol Acyltransferase (DGAT2) Gene from Oil Palm (Elaeis guineensis Jacq.) Mesocarp in Saccharomyces cerevisiae and Transgenic Arabidopsis thaliana - Jin, Yuanhang; Yuan, Yijun; Gao, Lingchao; Sun, Ruhao; Chen, Lizhi; Li, Dongdong; Zheng, Yusheng (Frontiers in Plant Science, 2017)
Oil palm (Elaeis guineensis Jacq.) is the highest oil-yielding plant in the world, storing 90% and 60% (dry weight) oil in its mesocarp and kernel, respectively. To gain insights into the oil accumulation mechanism, one of the key enzymes involved in triacylglycerol (TAG) biosynthesis, a type 2 diacylglycerol acyltransferase (DGAT) from oil palm, was characterized for its in vivo activity. EgDGAT2 is highly expressed in mesocarp during the last two developmental stages while large amounts of oil are accumulated at the highest rate during ripening. Heterologous expression of EgDGAT2 in mutant yeast H1246 restored TAG biosynthesis with substrate preference towards unsaturated fatty acids (16:1 and 18:1). Furthermore, seed-specific overexpression of EgDGAT2 in Arabidopsis thaliana enhanced the content of polyunsaturated fatty acids 18:2 and 18:3 (each by 6 mol%) in seed TAGs, when compared to that from wild-type Arabidopsis. In turn, the proportion of 18:0 and 20:0 fatty acids in seed TAGs from EgDGAT2 transgenic lines decreased accordingly. These results provide new insights into understanding the in vivo activity of EgDGAT2 from oil palm mesocarp, which will be of importance for metabolic enhancement of unsaturated fatty acids production.